GEM : A New International Macroeconomic Model - Bayoumi, Tamim (Occasional Papers; Occasional Paper ;, 2004)
Over the past two years, the IMF staff has been developing a new multicountry macroeconomic model called the Global Economy Model (GEM). This paper explains why such a model is needed, how GEM differs from its predecessor model, and how the new features of the model can improve the IMF's policy analysis. The paper is aimed at a general audience and avoids technical detail. It outlines the motivation, structure, strengths, and limitations of the model; examines three simulation exercises that have been completed; and discusses the future path of GEM.